A Comparative Study of Problem Solving Methods in Decision Support Systems - Obert, Obert; Fadlan, Muhammad (SENATIK STT Adisutjipto, 2018)
Decision Support System (DSS) as one of the disciplines related to decision making both by individuals and companies in general, has been widely applied in various fields such as health, education, energy and business. There are several choices of methods related to decision support systems that have been used globally. The selection of suppliers as one of the important agendas in a company requires a decision support system so that the selected supplier is the best according to the criteria set by the company. In this study several DSS methods are used to solve supplier selection problems. In addition, this study conducted a comparison of the three methods in the DSS, namely WSM, SAW and WP in the case of supplier selection. The main contribution of this article is to compare some DSS methods that have not been studied before. As a result, there are two of the three methods that have the same sequence of results, namely the SAW and WP methods. Where in both methods the A2 alternative has the highest value of 0.875 for SAW and 0.84 for WP results. While very different results are obtained using WSM calculations.